Pengaruh Literasi Keuangan, Payment Gateway, dan Peer to Peer Lending terhadap Peningkatan Pendapatan UMKM di Kabupaten Brebes - Tiya Aryana; Dumadi Dumadi; M. Badrun Zaman (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to find out and analyze the influence of financial literacy, payment gateways and peer to peer lending on increasing MSME income in Brebes Regency. Primary data were used in the study. The population in this study is all MSME actors in Brebes Regency who have used financial technology. Multistage cluster sampling technique with Slovin formula. Data analysis techniques with data quality test, classical asusmation test, multiple linear regression analysis and hypothesis test with the help of SPSS. The results of the study show that financial literacy has a positive and significant effect on increasing MSME income in Brebes Regency, payment gateways have a positive and significant effect on increasing MSME income in Brebes Regency, and peer to peer lending has a positive and significant effect on increasing MSME income in Brebes Regency as well as financial literacy, payment gateways and peer to peer lending have a positive and significant effect on increasing MSME income in Brebes Regency.